Comparison of oblique triangular configuration and inverted equilateral triangular configuration of three cannulated screws in treating unstable femoral neck fracture: A finite element analysis. Issue 2 (February 2022) - Zhang, Ru-Yi; Li, Jian-Tao; Zhao, Jing-Xin; Zhao, Zhe; Zhang, Li-Cheng; Yun, Cai; Su, Xiu-Yun; Tang, Pei-Fu
Highlights: The oblique triangle configuration with three parallel screws has a larger dispersion in the femoral neck isthmus than other configurations. We innovatively applied multiple material properties to simulate the stress, strain, and displacement of screws inside the femoral neck. This finite element analysis found that the screw stability of the OTC is higher than that of the traditional IETC. Abstract: Background: The cross-sectional area of three parallel screws might affect the stability of the internal fixation of femoral neck fractures. The screws fixed in the oblique-triangle configuration (OTC) were assumed to have a larger cross-sectional area, but the biomechanical stability has not yet been validated. In this study, finite element analyses were performed to compare the biomechanical properties of the internal fixation fixed by the OTC and the traditional Inverted Equilateral Triangle Configuration (IETC). Method: Pauwels type III fracture was established on the three-dimensional femoral model and three cannulated screws with the OTC and traditional IETC methods were applied. The oblique-triangle configuration with the largest area inscribed the femoral neck isthmus by the three screws was determined, the area and circumference of the cross-section formed by the OTC and IETC model were compared. Stress, strain, and displacement peaks of the two configuration models under different loads were compared. Twelve pairs of nodes on the fracture ends were selected and the displacement of the fracture ends was evaluated through the displacement between these nodes. Results: The area and circumference of the cross-section formed by the OTC were larger than those in the IETC model. The degree of stress dispersion around the screw holes in the OTC model was better than that of the IETC, but the stress distribution order of the three screws in the two models was consistent. The maximum stress, strain, displacement, and displacement of the fracture end in the OTC model were smaller than those in the IETC model. The stress, strain, displacement, and fracture end displacement peaks of the two fixed models gradually increase with the increase of loads. Conclusion: The oblique-triangle configuration showed superior mechanical properties than the IETC in finite element analyses. This study suggests that when three screws are fixed in parallel method, the larger the cross-sectional area of the screw configuration, the better stability of the internal fixation might be obtained. Furthermore, the biomechanical properties of various spatial configurations and screw holes of the three parallel screws need to be considered before clinical practice.